Understanding creativity in early childhood : meaning-making and children's drawings - Wright, Susan (Susan Kay) (London : SAGE, 2010)
Creativity is a key theme in early childhood studies at the moment & is increasingly highlighted in all manner of early childhood academic courses. This book will form the link between creativity & literacy with concrete examples of children's meaning making, as well as offering a protocol for students to follow
Includes bibliographical references and index
Keywords: Creative ability in children -- Study and teaching (Early childhood); Drawing